Adding physical activity to intensive trauma-focused treatment for post-traumatic stress disorder: results of a randomized controlled trial - Voorendonk, Eline M.; Sanches, Sarita A.; Tollenaar, Marieke S.; Hoogendoorn, Elisabeth A.; de Jongh, Ad; van Minnen, Agnes (Frontiers in Psychology, 2023)
Introduction This randomized controlled trial examined the effectiveness of physical activity added to an intensive trauma-focused treatment (TFT) for post-traumatic stress disorder (PTSD) in comparison to adding non-physical control activities. Methods A total of 119 patients with PTSD were randomly assigned to a physical activity condition (PA; n = 59) or a non-physical activity control condition (nPA; n = 60). The 8-day intensive TFT programme consisted of daily prolonged exposure, EMDR therapy, and psychoeducation, which was complemented with physical activities versus controlled mixtures of guided (creative) tasks. As a primary outcome, the change in clinician and self-reported PTSD symptoms from pre-to post-treatment and at 6 months follow-up were measured. Results Intent-to-treat linear mixed-effects models showed no significant differences between the PA and nPA conditions on change in PTSD severity. Clinician and self-reported PTSD symptoms significantly decreased for both conditions, with large effect sizes (e.g., CAPS-5 dpre-post = 2.28). At post-treatment, 80.0% in the PA, and 82.7% in the nPA condition no longer met the diagnostic criteria for PTSD. Regarding the loss of Complex PTSD diagnoses this was 92.5% and 95.0%, respectively. Conclusion Either with additional physical or non-physical activities, intensive TFT is very effective for the treatment of (Complex) PTSD, as reflected by large effect sizes and loss of diagnostic status in both groups. Clinical trial registration Trialregister.nl Identifier: Trial NL9120.